The 16S rRNA bacterial biodiversity of the flood water during massive flood session in Kota Bharu, December 2014 - Pwaveno Huladeino Bamaiyi; Nani Izreen Mohd Sani; Khatijah Mohamad; Nur Eizzati Badrul Hisham; Siti Bainum Che Rostman; Norsyamimi Farhana Mat Kamir; Mohd Norfaizull Mohd Nor; Mohd Azam Khan Goriman Khan (2015)
Introduction: Flood disasters are known all over the world to bring along with them